Oxidative stress and inflammation in the pathogenesis of neurological disorders: Mechanisms and implications - Umesh Chandra Dash; Nitish Kumar Bhol; Sandeep Kumar Swain; Rashmi Rekha Samal; Prabhat Kumar Nayak; Vishakha Raina; Sandeep Kumar Panda; Rout George Kerry; Asim K. Duttaroy; Atala Bihari Jena (Acta Pharmaceutica Sinica B)
Neuroprotection is a proactive approach to safeguarding the nervous system, including the brain, spinal cord, and peripheral nerves, by preventing or limiting damage to nerve cells and other components. It primarily defends the central nervous system against injury from acute and progressive neurodegenerative disorders. Oxidative stress, an imbalance between the body's natural defense mechanisms and the generation of reactive oxygen species, is crucial in developing neurological disorders. Due to its high metabolic rate and oxygen consumption, the brain is particularly vulnerable to oxidative stress. Excessive ROS damages the essential biomolecules, leading to cellular malfunction and neurodegeneration. Several neurological disorders, including Alzheimer's, Parkinson's, Amyotrophic lateral sclerosis, multiple sclerosis, and ischemic stroke, are associated with oxidative stress. Understanding the impact of oxidative stress in these conditions is crucial for developing new treatment methods. Researchers are exploring using antioxidants and other molecules to mitigate oxidative stress, aiming to prevent or slow down the progression of brain diseases. By understanding the intricate interplay between oxidative stress and neurological disorders, scientists hope to pave the way for innovative therapeutic and preventive approaches, ultimately improving individuals' living standards.